2018
DOI: 10.1007/s11845-018-1879-x
|View full text |Cite
|
Sign up to set email alerts
|

Largest known malignant solitary fibrous tumour of the pleura-extended resection warranting cardiopulmonary bypass support

Abstract: This case reports the largest known malignant solitary fibrous tumour of the pleura treated with en bloc surgical resection warranting the use of cardiopulmonary bypass support. A 60-year-old male presented with dyspnoea and a dry cough. Following extensive investigations, a radiological and histologic diagnosis of malignant solitary fibrous tumour of the pleura was made. This 4.3 kg tumour occupied the entire left hemithorax, involved the left lung and infiltrated into the pericardial cavity. Although the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…For patients with a large tumor or extensive adhesions, thoracotomy is often used, and in case of incomplete resection or recurrence, the secondary operation may be needed (51,52). Originated from the pleural wall, extrapleural resection can be carried out without removing the chest wall (53), and patients with pericardial cavity involvement may need cardiopulmonary bypass support (54). Preoperative percutaneous embolization has been reported to reduce the risk of intraoperative bleeding significantly; however, SFTP embolization may lead to a rare potential life-threatening complication (55).…”
Section: Discussionmentioning
confidence: 99%
“…For patients with a large tumor or extensive adhesions, thoracotomy is often used, and in case of incomplete resection or recurrence, the secondary operation may be needed (51,52). Originated from the pleural wall, extrapleural resection can be carried out without removing the chest wall (53), and patients with pericardial cavity involvement may need cardiopulmonary bypass support (54). Preoperative percutaneous embolization has been reported to reduce the risk of intraoperative bleeding significantly; however, SFTP embolization may lead to a rare potential life-threatening complication (55).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 5-27% of SFTs occur in the head and neck region [39] with the oral cavity [40] and the orbit [39] being the most commonly affected sites. A few studies showed that pelvic [27,30,41], abdominal [27,42], and pleural [27,40,43] SFTs tend to be larger than tumors appearing in other locations, and extrapleural SFTs may show potentially malignant behavior [44], especially those with limb localization [45]. Generally, over the years, SFTs have been described in various localizations, including the liver [46,47], kidney [48][49][50], pancreas [23,51,52], sigmoid colon [31], mesocolon [14], omentum [53,54], urinary bladder [55], caecum wall [56], mesorectum [41], prostate [57], spermatic cord [58], testis [59], scrotum [60], female gynecological tract, especially the vulva [61,62], vagina [63], breast [64][65][66], heart and pericardium [33,67,68], epicardium [69], pulmonary artery [70], trachea…”
Section: Anatomical Locationmentioning
confidence: 99%